Comparison of the patient and partner satisfaction with 700CX and Titan penile prostheses - Javier Romero Otero; César Rojas Cruz; Borja García Gómez; Joaquim Sarquella Geli; Jose Medina Polo; Eduard Ruiz Castañé; Alfredo Rodríguez Antolín (Asian Journal of Andrology, 2017)
Most widespread three-component penile prosthesis models are 700CX™ and Titan ® . Our purpose is to assess patient and partner satisfaction after the first implant. This is a multicenter, retrospective, nonrandomized study in which all patients who met the inclusion criteria between 2009 and 2013 were included. In total, 248 patients agreed to participate. To evaluate patient satisfaction, a validated but modified 11-question questionnaire was completed (EDITS); and a nonvalidated two-item questionnaire was given to the partner. Statistical analysis used an ordinal logistic regression model. Two hundred and forty-eight patients (194 with 700CX™ vs 54 with Titan®) and 207 couples completed the questionnaire (165 with 700CX™ vs 42 with Titan®). Overall satisfaction was high. Both showed great reliability for sexual intercourse and high compliance with prior expectations. Most patients were able to manage the penile prosthesis correctly within 6 months. Postoperative penile shortening led to some dissatisfaction in 42% and 46% of cases (700CX™ /Titan®). Significant differences were found in three questions of patients′ questionnaire. There were more patients satisfied with the 700CX™ (P = 0.0001). No patient with Titan® implant took longer than 6 months to optimal management. Only 4% of patients with 700CX™ implant were dissatisfied with the deflation, in contrast to 24% with the Titan® (P = 0.0031). Of the two partners′ questions, one showed a statistically significant difference (P = 0.0026). It seems that group 700CX™ would recommend to re-implant the prosthesis with a greater tendency. The overall satisfaction was very high for both prostheses. The final aspect of the erected and flaccid penis was satisfactory, but both groups showed significant discontent with its final size. Partners′ overall satisfaction was high.